1998
DOI: 10.1080/07315724.1998.10718809
|View full text |Cite
|
Sign up to set email alerts
|

Cookies Enriched with Psyllium or Oat Bran Lower Plasma LDL Cholesterol in Normal and Hypercholesterolemic Men from Northern Mexico

Abstract: These results indicate that psyllium and oat bran are efficacious in lowering plasma LDL cholesterol in both normal and hypercholesterolemic individuals from this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 33 publications
4
30
0
Order By: Relevance
“…Similar results were shown by other authors (Davidson et al, 1998;Romero et al, 1998). However, Rodríguez-Morán et al (1998) observed a significant increase in this parameter after the administration of 15 g psyllium daily to type 2 diabetic patients.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar results were shown by other authors (Davidson et al, 1998;Romero et al, 1998). However, Rodríguez-Morán et al (1998) observed a significant increase in this parameter after the administration of 15 g psyllium daily to type 2 diabetic patients.…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, our results were slightly lower than those found by Anderson et al (1999) in men with type 2 diabetes and hypercholesterolaemia after 8 weeks receiving 10.2 g psyllium daily. Romero et al (1998) observed that LDL cholesterol concentrations were reduced by an average of 22.6 and 26% after administering 1.3 g=day of psyllium to healthy volunteers. In the same way, other authors (Rodríguez-Morán et al, 1998;Segawa et al, 1998) found a significant reduction in total and LDL cholesterol.…”
Section: Discussionmentioning
confidence: 98%
“…Two randomised controlled trials were identified that presented evidence on psyllium supplements in relation to fasting blood lipids (total cholesterol; HDL-and LDLcholesterol and triacylglycerol concentration) (Bell et al, 1990;Romero et al, 1998). One trial was subsequently identified in the update search (Pal et al, 2011) (Spiller et al, 1979;Stevens et al, 1988;Marteau et al, 1994;Vuksan et al, 2008).…”
Section: Fasting Blood Lipidsmentioning
confidence: 99%
“…Seven randomised controlled trials were identified that presented evidence on oat bran and β-glucan supplementation in relation to fasting total cholesterol, HDL-and LDLcholesterol concentration (Swain et al, 1990;Johnston, 1998;Romero et al, 1998;Saltzman et al, 2001;Davy et al, 2002b;Chen et al, 2006;Keenan et al, 2007). All of the trials, except one (Swain et al, 1990), also presented evidence on oat bran and β-glucan supplementation in relation to fasting triacylglycerol concentration.…”
mentioning
confidence: 99%
See 1 more Smart Citation